Knowledge and practice on drug compliance among hypertensive patients in field practice area of a tertiary health care institute in Haryana - Singh, Navraj; Rajput, Meena; Khanna, Pardeep; Bansal, Kanika; Ranjan, Ravish; Kaur, Manpreet (International Journal Of Community Medicine And Public Health, 2021)
Background: Hypertension contributed 1.6 million deaths and 33.9 million disability-adjusted life years lost in 2015. It has been documented that decrease in systolic BP by 10 mm Hg leads to 22% reduction in CHD and 41% reduction in stroke, which can be achieved by better drug compliance. Knowledge of patients regarding hypertension and its associated complications and drug compliance in hypertension is the key to achieve compliance to medication and control of blood pressure. Aim of study was to find out the proportion of drug compliance among hypertensive patients and to identify various factors associated with non-compliance to drugs. Methods: Descriptive, cross-sectional study was done in out-patient departments of Community Health Centre Dighal and Civil Hospital Beri. 400 follow up patients of hypertension who were 30 years and above taking treatment of hypertension from last 1 year, attending OPD. Medication adherence was assessed using Morisky medication adherence scale (MMAS-8). Results: 72.5% study subjects showed low level of adherence. Low adherence was maximum in the age group of 51-60 years (77.6%) and most common reason for non-compliance to drugs was observed to be forgetfulness (59.3%). Patients unaware of the complications were having low adherence to medication as compared to counterpart and this association was observed to be statistically significant (p value≤0.05). Conclusions: The result of this study is of value to health care providers to prevent treatment failure due to noncompliance and prevent premature deaths.